Experimental plastic visions to benefit from it in implementing innovative clothes for women - Shimaa Mohamed Amer Nasef; Shimaa alsakhawy (Maǧallaẗ Al-Turāṯ wa Al-Taṣmīm, 2022)
As a result of the emergence of many modern materials such as plastics, plastics, polyester, fiberglass and some other industrial materials, this huge amount of different materials, whether in terms of their textures, colors, or their distinctive plastic capabilities, each from the other. raw materials, and the artist had to be in constant contact with these modern materials on the one hand, with a continuous quest on the other hand to research, train and know realistic information about them, which resulted in a great development in the various fields of plastic arts (Manar Mahmoud - 2013-389).The more the designer’s knowledge of the capabilities of the material and the methods of processing and dealing with it, this leads to the diversity of his imaginative ideas and his ability to be creative (Heba Jalal -2007-170), and from here comes the role of the designer in the search for new designs trends that contain unconventional materials and different techniques, so the current study turned to The use of plastics in the field of clothing as an innovative approach, and from here it was possible to identify the research problem in the following questions: The possibility of benefiting from plastic bags in the implementation of clothing pieces with innovative design and keeping pace with fashion, what are the appropriate techniques for producing clothing pieces of plastics (plastic bags)? Do the executed designs achieve functional and aesthetic values?